Status epilepticus-Detection and treatment in the intensive care unit - Reindl, Caroline; Madzar, Dominik; Hamer, Hajo (Der Nervenarzt, 2022)
Status epilepticus is characterized by persistent or repetitive seizures which, without successful treatment, can lead to neuronal damage, neurological deficits and death of the patient. While status epilepticus with motor symptoms can usually be clinically diagnosed, nonconvulsive status epilepticus is often clinically overlooked due to its ambiguous semiology, so that electroencephalography (EEG) recording is necessary. The treatment of status epilepticus is performed in four treatment steps, whereby a difficult to treat status epilepticus is present from the third step at the latest and intensive medical care of the patient is necessary. Timely initiation of treatment and sufficient dosage of anticonvulsive medication are decisive for the success of treatment. There is little evidence for the "late " stages of treatment. Intensive medical measures pose the risk of complications that worsen the prognosis. Especially in nonconvulsive status epilepticus, the use of anesthetics must be weighed against possible complications of mechanical ventilation.
CRIS-Team WoS Importer:2023-01-13